A New Class of Wolf-Rayet Stars: WN3/O3s. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Massey, Philip; Neugent, Kathryn F.; Morrell, Nidia; John Hillier, D.
Abstract: Our new survey for Wolf-Rayet stars in the Magellanic Clouds is only 15% complete but has already found 9 new Wolf-Rayet (WR) stars in the Large Magellanic Cloud (LMC). This suggests that the total WR population in the LMC may be underestimated by 10-40%. Eight of the nine are of the WN subtype, demonstrating that the "observed" WC to WN ratio is too large, and is biased towards WC stars. The ninth is another rare WO star, the second we have found in the LMC in the past two years. Five (and possibly six) of the 8 WNs are of a new class of WRs, which pose a significant challenge to our understanding. Naively we would classify these stars as "WN3+O3V, " but there are several reasons why such a pairing is unlikely, not the least of which is that the absolute visual magnitudes of these stars are faint, with MV -2.3 to -3.1. We have performed a preliminary analysis with the atmospheric code CMFGEN, and we find that (despite the faint visual magnitudes) the bolometric luminosities of these stars are normal for early-type WNs. Our fitting suggests that these stars are evolved, with significantly enriched N and He. Their effective temperatures are also normal for early-type WNs. What is unusual about these stars is that they have a surprisingly small mass-loss rate compared to other early-type WNs. How these stars got to be the way they are (single star evolution? binary evolution?) remains an open question. For now, we are designating this class as WN3/O3, in analogy to the late-type WN "slash" stars.